ANALYSIS OF CHARACTER EDUCATION VALUES IN THE KUDA LUMPING ART PERFORMANCE IN SIDOGEDE VILLAGE: ANALISIS NIlAI PENDIDIKAN KARAKTER PADA PERTUNJUKAN KESENIAN KUDA LUMPING DI DESA SIDOGEDE - Erfina Firmala; Maulidiawati (SOSIOEDUKASI, 2025)
This study analyzes the character education values contained in the Kuda Lumping art performance in Sidogede Village, focusing on the role of traditional art as an educational medium. The main problem raised is the lack of in-depth understanding of the function of the Kuda Lumping performance, which is often considered only as entertainment, even though it has great potential as a means of character building. The purpose of this study is to identify, describe, and analyze the character education values that appear in the performance, and to understand how these values are internalized by the artists and the community. The method used is a qualitative approach with a case study design, which allows the researcher to dig deep into the data. Primary data were obtained through direct observation, in-depth interviews with dancers and studio owners, and visual and audio documentation. Secondary data are in the form of activity documentation and reports. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. Data validity was guaranteed by triangulation techniques. The results show that the Kuda Lumping performance in Sidogede Village contains at least eight main character values, with varying levels of emergence: discipline, cooperation/mutual assistance, and togetherness (very high); responsibility, self-confidence, love of culture/nationalism, and consistency and loyalty (high); and religiousness (moderate). These values are manifested in various aspects, ranging from a strict training schedule, synergy between performers, to community involvement across ages. Based on these findings, it can be concluded that the Kuda Lumping art performance in Sidogede Village functions not only as entertainment, but also as an effective medium and informal school that consistently instills noble values in its performers and the community. This art plays an important role in preserving local culture while forming strong character, making it a relevant and contextual non-formal education model.